Buildings, Faces, Songs of Alienation: How Interiority Transforms the Meaning Out There - De Kock, Peter Marthinus (Interiority, 2020)
This paper presents a theoretical framework that explores visual meaning in the design and use of interior space. It is comprised of three main parts. The first outlines the framework and draws on several key theories. The second introduces three very different constructs as case studies that in#uence (or are a product of) spatial quality, namely: buildings, faces, and songs of alienation. The third part is a discussion about how each of these three constructs are linked to each other as well as to the idea of interiority. While architectural forms are containers of meaning, the way in which interior space is curated is driven by deeper meaning–one that transcends form and function because people ultimately produce the meaning. And because each person is different, the conditions of interiority (in this case, the meaning that resides within each person) drives the meaning of external constructs that act as enclosures of meaning (buildings and their interiors). The findings are that the mind and body can be projected beyond the facade and into the spaces contained in the buildings we occupy. The role of technology is also important because changes in technology help mediate the process of linking the meaning inside with the meaning out there.